Capacities, internal conditions of organization and relationship and their impacts on the coordination of an environment secretariat (Research, Society and Development, 2021)
Coordination is a challenge for public organizations, as it does not always have the capacity to guide interests towards common goals. In view of this, this work aims to analyze the capacities, the internal conditions of organization and relationship of an Environment Secretariat of a municipality in the West of Pará, with the perspective of deepening the understanding about the challenges of coordination in a public organization in the context Amazonian. To this end, interviews were conducted with managers and employees to capture perceptions and positions about organizational actions. The interviews were analyzed following the principles of content analysis with the aid of textual statistics software. The results obtained show that the organization seeks to fulfill its objectives, however there are limitations in the organization and in the relationship that produces a segregation and reduced flow of information between sectors between functional areas, compromising the coordination process. It is found that the challenges of coordination are not linked only to the characteristics of the bureaucracy, but it permeates the good organization and internal relationship.